Proposal for an efficient, minimal electrodiagnostic protocol for confirmation of clinically diagnosed ulnar nerve entrapment neuropathy at the elbow - Kurver, Anne; Meulstee, Jan; Bartels, Ronald H. M. A.; Verhagen, Wim I. M. (Frontiers in Neurology, 2025)
IntroductionThe clinical diagnosis of ulnar nerve entrapment at the elbow can reliably be made based on typical clinical symptoms of UNE. In the present study, we constructed an efficient, minimal electrodiagnostic protocol for confirmation of clinically diagnosed UNE.MethodsA prospective cross-sectional cohort observational study was conducted among patients with clinical suspicion of UNE. In all, 210 arms were included, each examined according to a standard neurophysiological protocol.ResultsNerve conduction studies (NCS) indicated abnormalities in 60.5% of the cases. Of these, 84.3% had abnormal NCS results for the abductor digiti quinti muscle (ADV). The first dorsal interosseous muscle (FDI) and sensory NCS were abnormal in 68.5 and 59.1% of these cases, respectively.ConclusionWe recommend starting with NCS of the ADV for cases requiring only one abnormal test is needed to confirm the clinical diagnosis of UNE, followed by sensory NCS if the NCS of the ADV is normal.